The Correlation between Low Birth Weight and Stunting in 24-59 Month Children in Haya-Haya Village, Western Limboto Sub-District, Gorontalo Regency - Bun Yamin M. Badjuka (Universitas Wiralodra, 2020)
Undergoing relatively slower growth, infants with low birth weight (henceforth, LBW) sometimes suffer from digestive tract disorders that leads to deficiency of nutrients supply within the body. The 2018 data in Gorontalo Regency reported that 312 under-fives suffer from LBW. This study intends to analyze whether or not LBW contributes to stunting cases in 24-59 months infants in Haya-haya village, Western Limboto sub-district, Gorontalo regency. The analytical observational survey study employed cross-sectional approach. The study treated the population of all babies with LBW as the sample by total sampling technique. Moreover, it involved LBW as the independent variable and stunting as the dependent variable. The statistical test result indicates that χ2count > χ2 table with ρ value of 0.00 < 0.05; therefore, signifying that H0 is denied and Ha is accepted. All in all, there is a significant correlation between LBW and stunting cases in 24-59 months babies in the research site.